2014
DOI: 10.1038/modpathol.2013.170
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoid adenocarcinoma of the lung: report of five cases and review of the literature

Abstract: The current diagnostic criteria for hepatoid adenocarcinoma of lung include typical acinar or papillary adenocarcinoma and a component resembling hepatocellular carcinoma and expressing a-fetoprotein (AFP). Distinguishing hepatoid adenocarcinoma of lung from hepatocellular carcinoma metastatic to lung is difficult in patients with both lung and liver masses and in patients at risk for lung and liver cancer because of smoking and viral hepatitis, respectively. We studied morphologic features of hepatoid adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 18 publications
(36 reference statements)
8
103
1
2
Order By: Relevance
“…Tumor cells have eosinophilic cytoplasm, centrally located nuclei proliferating in a trabecular pattern, and express AFP, HepPar1, HEA125 and MOC31 (1,2). The lung is the primary site in approximately 5% of cases of HAC (1).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells have eosinophilic cytoplasm, centrally located nuclei proliferating in a trabecular pattern, and express AFP, HepPar1, HEA125 and MOC31 (1,2). The lung is the primary site in approximately 5% of cases of HAC (1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the diagnostic criteria for this cancer included the presence of elevated levels of alpha-fetoprotein. However, quite a few studies have shown that AFP is not specific for hepatoid adenocarcinoma of the lung, being more frequently associated to hepatocellular The expression of alpha-fetoprotein is not mandatory for the diagnosis, as long as other immunohistochemical markers of hepatic differentiation are expressed 2,6 . Therefore, the presented case meets criteria for the diagnosis of hepatoid adenocarcinoma of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly affected organ is the stomach (63%) but it may affect others, such as ovary (10%), lung (5%), bladder (4%), pancreas (4%) and uterus (4%) 2 . Hepatoid adenocarcinoma of the lung is an extremely rare form, with only 20 cases described 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatoid carcinomas may also express MOC31 and mCEA, which are infrequently expressed in HCCs. 160 In a recent study on 8 hepatoid carcinomas, Chandan et al 161 demonstrated positive stains for Hep Par 1, Arg-1, GPC3, and AFP in 8 (100%), 5 (62.5%), 4 (50%), and 4 (50%) cases, respectively. Canalicular pCEA pattern was observed in 3 cases (37.5%).…”
Section: Distinction Between Hepatoid Carcinoma and Hccmentioning
confidence: 95%